Complications of Transverse Distal Penile Island Flap: Urethroplasty of Complex Anterior Urethral Stricture - Olajide, Abimbola O.; Salako, Abdulkadir A.; Aremu, Ademola A.; Eziyi, Amogu K.; Olajide, Folakemi O.; Banjo, Oluseyi O. (Urology Journal, 2010)
PURPOSE: To report the complications of transverse distal penile island flap urethroplasty for urethral reconstruction in adult patients with long/ multiple segments anterior urethral stricture. MATERIALS AND METHODS: This prospective study was carried out on 55 patients with complex anterior urethral stricture to study complications of transverse distal penile island flap urethroplasty in two teaching hospitals between June 2002 and December 2008. Pre-, intra- and postoperative information were collected on a pro forma to generate data, which was analyzed. RESULTS: The patients’ mean age was 43.83 years (range, 19 to 73 years). The leading etiology of the stricture was urethral inflammation (76.4%) with the commonest complication being infection: wound infection in 9.1%, urosepsis in 3.6%, and epididymo-orchitis in 1.8% of the subjects. CONCLUSION: Transverse distal penile island flap urethroplasty has a remarkable outcome in treatment of a long/multiple segment urethral stricture with few manageable complications.